THE INFLUENCE OF WORK MOTIVATION AND ORGANIZATIONAL COMMITMENT ON PERFORMANCE THROUGH JOB SATISFACTION (A STUDY ON PROFESSIONAL ASSISTANTS OF THE MINISTRY OF VILLAGE IN KONAWE DISTRICT) - Aguslan, Aguslan; Murdjani Kamaluddin; Muhamad Masri (Journal of Information Systems Management and Digital Business, 2024)
This study aims to examine the impact of Work Motivation and Organizational Commitment on Performance through Job Satisfaction among the Professional Support Staff at the Ministry of Village in Konawe Regency. The population in this research consists of 119 Professional Support Staff members at the Ministry of Village in Konawe Regency. Data analysis for this study utilized SmartPLS version 3.0. The results of this research indicate that Work Motivation has a positive and significant influence on job satisfaction. Organizational commitment also has a positive and significant influence on job satisfaction. Work Motivation has a positive and significant influence on performance. Organizational commitment similarly has a positive and significant influence on performance. Job satisfaction has a positive and significant influence on performance. Work Motivation has a positive and significant influence on performance through job satisfaction. Organizational commitment also has a positive and significant influence on performance through job satisfaction